Pendidikan Anak Usia Dini di Awal Sekolah Dasar Melalui Joyfull Learning: Catatan Kritis Terhadap Pembelajaran Menggambar Anak - Nur Hamzah (PSGA LP2M IAIN Pontianak, 2014)
One of the urgent aspects which has to be provided by adults in a child’s potency is the ability of drawing. Furthermore, the importance of drawing has a relevancy with the motoric trait development in children. Besides, drawing is able to enhance the ability of right brain as a visualization. This brain, moreover, has an essential part to strengthen all of intellectual activities. Nevertheless, it is slightly hard to expect that drawing will maximally contribute in children especially in an elementary school. Drawing which has been done in the elementary school is unfortunately accomplished without a construction concept by the teacher. This writing is a critical annotation to a drawing lessonat school, especially in early childhood education programs.